Wawacan Sama'un : edisi teks dan analisis struktur - Christomy, T. Tommy, 1959- (Jakarta : Djambatan, 2003)
Criticism on Wawacan Sama'un, a Sundanese story in verse
Revision of the author's thesis (master's)--Universitas Indonesia, 1992
Daftar Pustaka : p. 341-345
In Indonesian, with original text in Sundanese
Keywords: Manuscrpts, Arabic -- Indonesia -- Translations